2023
DOI: 10.1136/bmjopen-2022-069905
|View full text |Cite
|
Sign up to set email alerts
|

Comparing trends in mid-life ‘deaths of despair’ in the USA, Canada and UK, 2001–2019: is the USA an anomaly?

Jennifer Beam Dowd,
Colin Angus,
Anna Zajacova
et al.

Abstract: ObjectivesIn recent years, ‘deaths of despair’ due to drugs, alcohol and suicide have contributed to rising mid-life mortality in the USA. We examine whether despair-related deaths and mid-life mortality trends are also changing in peer countries, the UK and Canada.DesignDescriptive analysis of population mortality rates.SettingThe USA, UK (and constituent nations England and Wales, Northern Ireland and Scotland) and Canada, 2001–2019.ParticipantsFull population aged 35–64 years.Outcome measuresWe compared all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our analyses did not separate the UK into its constituent countries but previous work has shown much higher midlife mortality in Scotland, with drug mortality in recent years even higher than it is in the USA. 24 Overall, our results confirm the divergence of UK mortality from peer countries, which, like the USA, is more pronounced in the younger middle-aged groups and in females. Although the US mortality crisis has received substantial attention, a greater understanding of the causes behind the stagnation in the UK and prospects for the future is needed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our analyses did not separate the UK into its constituent countries but previous work has shown much higher midlife mortality in Scotland, with drug mortality in recent years even higher than it is in the USA. 24 Overall, our results confirm the divergence of UK mortality from peer countries, which, like the USA, is more pronounced in the younger middle-aged groups and in females. Although the US mortality crisis has received substantial attention, a greater understanding of the causes behind the stagnation in the UK and prospects for the future is needed.…”
Section: Discussionsupporting
confidence: 77%
“…25 Next, our data did not allow examination of variation in mortality by subgroups and regions within countries. Previous studies have suggested large mortality differences between socio-economic groups 26 , 27 and regions in the USA and the UK 24 , 28 so analysis at the national level alone may obscure important trends in certain groups.…”
Section: Discussionmentioning
confidence: 99%
“…The largest contributor to the growth in excess US deaths between 1999 and 2019 was the increase in drug poisonings, alcohol-related mortality, and suicide, often conceptualized as "deaths of despair". [18][19][20][21][22] The US had death rates similar to peers for these causes in 1999.…”
Section: Discussionmentioning
confidence: 97%
“… 9 Across a similar time period between 2010 and 2019 all-cause mortality rates in the USA among men aged 35–44 years rose from 212/100 000 to 257/100 000, and in women from 128/100 000 to 143/100 000. 10 Across all HICs, the GBD study has estimated that the probability of dying from any cause between ages 15 and 60 years is unacceptably high, especially for men, at 10% (14% in USA, 8% in UK, Australia, New Zealand and Canada). 1 The GBD probability estimates for dying between years 15 and 60 are also unacceptably high in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“… 8 18 While it has been suggested that deaths of despair are unique to the USA, 8 18 19 there is growing recognition that these patterns of deaths (eg, substance use deaths) are now rising throughout other HICs, although at a slower pace. 10 11 20 This emergent epidemic is primarily occurring within young working-age adolescents and young to middle-aged adults in the general, rather than clinical, population, who are participating in health-compromising behaviours potentially caused by exposure to early-life and/or present deteriorating social and economic conditions (eg, austerity). 17 19 21–23 …”
Section: Introductionmentioning
confidence: 99%